(untitled) (Asian Education Studies, 2022)
Identity and investment have become the two most significant concepts in the field of second language acquisition and English as a foreign language (EFL). Conducted through semi-structured interviews and thematic analysis, this study focused on the narrative cases of two EFL students in the bilingual higher education project, revealing their identity changes throughout the project from a poststructural perspective. Their investment in foreign language learning was also fully explored through the analysis of a series of semi-structured interviews and diary data. The findings of this study show that identities are multiple, dynamic and contradictory, both emergent in changing sociocultural contexts and driven by individuals‟ own agency, and participants‟ identities also oscillate between the imagined communities and communities of practice. The investment of these two students in bilingual literacy is also mediated by three intertwined structures: capital, ideology and identity. In addition, participants‟ second language investments vary considerably, due to their different agency in English language learning.